Understanding the maternal contributors to caesarean section rates: A hospital based study in Makassar, Indonesia - Putri, Rezki Suci Amalia; Yunus, Purnamaniswaty; Rahim, Rosdianah; Fitriani, Rini; Syatar, Abdul (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Caesarean section (CS) is a surgical procedure performed when vaginal delivery is not possible due to medical or non-medical indications. The increasing prevalence of CS worldwide has raised concerns regarding maternal and neonatal health. Objectives: This study aims to identify maternal factors contributing to the increased incidence of CS at Sitti Khadijah 1 Maternity Hospital, Makassar, for the period of January 1 – December 31, 2023. This research provides a unique contribution by analyzing CS prevalence and risk factors in a private Islamic maternity hospital, a setting underrepresented in national data. Furthermore, quantitative evaluation using multivariate analysis was conducted to determine the most dominant risk factors, supporting evidence-based prioritization in clinical decision-making and antenatal care planning in similar urban Indonesian contexts.Methods: A cross-sectional study was conducted using secondary data from medical records of mothers who delivered at Sitti Khadijah 1 Maternity Hospital in 2023. Maternal age, history of CS, premature rupture of membranes (PROM), gestational age, and preeclampsia were analyzed. Statistical tests included Chi-Square and multivariate analysis.Results: Of 341 deliveries, 300 (88.0%) were CS cases. Significant associations were found between CS and history of CS (p=0.004), preeclampsia (p=0.000), and PROM (p=0.000), while maternal age (p=0.751) and gestational age (p=0.183) were not significant. Mothers with a previous CS had a 99.0% likelihood of undergoing repeat CS. Preeclampsia strongly predicted CS, with 94.8% of cases delivered surgically. PROM was also a determinant, with 96.3% undergoing CS. Multivariate analysis confirmed history of CS as the strongest predictor (OR=19.689; 95% CI 2.589–149.737; p=0.004).Conclusion: History of CS, preeclampsia, and PROM are significant factors associated with CS. The risk of CS is significantly associated highest with history of CS. These findings highlight the need for improved maternal healthcare strategies to manage high-risk pregnancies and reduce unnecessary CS procedures.